MOTIVATION BY INDONESIAN EFL HIGH SCHOOL LEARNERS: A COMPARISON OF ORPHAN AND NON ORPHAN LEARNERS - Rachell Fattama Az Zahrah; Sahiruddin Sahiruddin; Nurul Chojimah (EDUCAFL : Journal of Education of English as Foreign Language, 2022)
Motivation has been considered the most contributing factor to the success of language learning. Motivation has some factors that affect the high or low scale of the motivation. Parents' support, for instance, claimed that parents involve the students' motivation, then what if the students who do not have parents or called as the orphan? This study scrutinizes the comparison of the orphan and non orphan student’s motivation.The design of this study was quantitative design, in which the study examined the difference between orphan and non-orphan students in terms of motivation in learning English as measured by questionnaire response scores. An Independent t-test was computed to answer research question. The participants involved in this study were a hundred students from the secondary level, including junior high school (n=66) and senior high school (n=34) participating in this study fifty (n=50) the students were orphans, and fifty (n=50) others were non-orphan.The result of the research question demonstrates that non-orphan Indonesian EFL  learners had higher individual motivation and social motivation in learning English compared to orphan learners for individual motivation and social motivation. Since, the orphan has a lower motivation, the reasons for that phenomenon can be a potential further study.